Letters from Cumann na mBan to the Irish Volunteers regarding the organisation, - Cumann na mBan (1918)
Includes letter addressed to Fóirín Ua Donncadha [Florence O'Donoghue] concerning a Cork City Hall event. Copy letter on behalf of Cumann na mBan Executive lists of suspended members. With annotations.